New ceramic surface design learn to inlay, stamp, stencil, draw, and paint on clay - Hatch, Molly 1978- (Beverly, Massachusetts Quarry Books, 2015)
A fully-illustrated manual covering a wide range of creative surface decoration techniques presented in an approachable and accessible format.
Introduction -- Getting ready -- Finding inspiration -- Composition and form -- Making lines -- Texture -- Shape -- Templates -- Resources -- Recipes -- Glossary -- Artist directory -- About the author -- About the photographer -- Acknowledgments.
Keywords: Pottery craft; Ceramics -- Surfaces; Glazing (Ceramics)